Fighting Marginality: The Global Moment of 1917-1919 and the Re-Imagination of Belonging - Fabian Krautwald; Thomas Lindner; Sakiko Nakao (L'Atelier du CRH)
The transformation of the international order brought about by the First World War engendered strange bedfellows. At the end of the war, Pan-Africanists, Mexican anti-imperialists, and German colonialists all shared a sense of marginality, finding themselves excluded from the deliberations over the new world order. We take this shared sense of marginality as the starting point for an exploratory comparison of the three groups. All three appropriated globally-circulating ideas of liberalism and communism for their own ends in their desire to overcome their persistent or newly imposed marginal status. We argue that the ensuing processes of adaptation allowed these actors to form ideologically — and, at times, geographically — broader senses of belonging. Furthermore, we problematize the concept of global moments by highlighting how the three groups developed similar, if not necessarily congruous perceptions of the conjuncture of 1917-19